Analisa Elemen Arsitektur Cina pada Bangunan Lokal - Winata, Henry; Maulana, Candra; Rusydi, Muhammad; Kusuma, Tiyas; Basri, Dian Monica Erveline (Local Engineering, 2026)
Indonesia is a country with various ethnicity and culture. One with the most population compared to another foreign ethnic is Chinese. This results in the existence of so many buildings influenced by Chinese architecture, such as: houses, temples, schools and others. It’s quite intriguing how school design is using Chinese architecture, considering that it is a public facility which has fixed facilities, and strictly monitored by government’s regulation. This is the main reason of choosing Tzu Chi school as a case study in this research. The goal of doing this research is to know which Chinese architecture character is used in the building design. The research variables are: roof, door, window, column and stairs. The research method is qualitative-descriptive, by comparing the variables of the case study with the reference, and then describing the observation in narrative manner. Based on the research, it is concluded that Tzu Chi school is implementing Chinese architecture in its design.